The Influence of E-Service Quality, Price Perception, and Sales Promotion on Customer Loyalty Through Customer Satisfaction on the Gojek Application - Andriani, Nia; Nurbaiti, Nurbaiti; Aisyah, Siti (JESI (Jurnal Ekonomi Syariah Indonesia), 2024)
This research aims to determine the influence of e-service quality, price perception, and sales promotions on customer loyalty through customer satisfaction for Gojek transportation customers. This research approach uses a quantitative approach. The technique used in this research is purposive sampling technique. The population in this study was 1,128 people and the sample was 92 FEBI UINSU students in the class of 2019. The data analysis technique for this research was Path Analysis using Multiple Linear Regression Analysis with 2 substructures in the form of the F Test to determine the influence of the independent variables on the dependent variable simultaneously, and the t-test was processed using the Statistical Program for Social Science (SPSS) version 29 application. The results of the research explain that there is an influence of e-service quality, price perception, and sales promotions on customer loyalty. And there is an influence between e-service quality, price perception, and sales promotion on customer satisfaction. E-service quality, price perception, and sales promotions can directly influence the customer loyalty variable without any intervention, namely customer satisfaction.